Assessment of body mass index, polygenic risk score, and development of colorectal cancer - Chen, Xuechen; Li, Hengjing; Mandić, Marko; Hoffmeister, Michael; Brenner, Hermann (JAMA network open, 2022)
Excess weight, the prevalence of which is high and increasing in many countries, is linked to multiple adverse health outcomes, including increased colorectal cancer (CRC) risk. Better communication of health risks associated with excess weight might support efforts of prevention.
Gesehen am 15.11.2023